THE IMPACT OF TASK-BASED INSTRUCTION IN IMPROVING STUDENTS’ AUTONOMOUS IN WRITING AT MECHANICAL ENGINEERING PROGRAM IN UKI TORAJA, INDONESIA - Baka, Charlie (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
This study is qualitative research which employs case study on Task-Based Instruction (TBI) impact on students’ autonomous learning at Mechanical Engineering in Teaching English at UKI utilized online questionnaire and interview student’s journal reflection as well as documentation. The research was carried out at Mechanical Engineering Department UKI Toraja, which located in Tanah Toraja, South Sulawesi. The research used purposive sampling method which involved 12 lecturers; 3 English lectures who were currently implementing Task-Based Instruction (TBI) in teaching English for Mechanical Engineering, 35 students of Mechanical Engineering, at UKI Toraja as the participants of this research. The data was analyzed by thematic analysis, content analysis, and document analysis. The findings reveal that different types of tasks and digital tools promote learner autonomy in different ways. Writing assignments allow students to work independently to choose a topic, create their written content, and choose online application software that allows them more freedom in exploring the understanding of a particular topic. Learning outcomes are characterized as Autonomous Task-Based Instruction in Teaching Writing because this strategy contributes to the degree of learning independence.